Relationship between leadership strengths and imposter phenomenon in pharmacy professionals and students - Jaclyn Cole; Anthony DeClue; Jordan Ballou; Kristy Brittain; Melissa Ruble; Caroline Sasser; Caroline Ko; Melissa Noble; Brandon Jennings (INNOVATIONS in Pharmacy)
Objective: To identify trends between leadership strengths and the prevalence of imposter phenomenon (IP), with a secondary focus on growth mindset.